2022
DOI: 10.1002/oby.23347
|View full text |Cite
|
Sign up to set email alerts
|

Trends in spontaneous physical activity and energy expenditure among adults in a respiratory chamber, 1985 to 2005

Abstract: Objective Fidgeting, a type of spontaneous physical activity (SPA), has substantial thermogenic potential. This research aims to examine secular trends in SPA and energy expenditure (EE) inside a respiratory chamber. Methods From 1985 to 2005, healthy adults (n = 678; mean age: 28.8 years; men: 60%; 522 Indigenous American, 129 White, and 27 Black) had a 24‐hour stay in the respiratory chamber equipped with radar sensors. Body composition, glucose tolerance, fasting insulin, insulin action (hyperinsulinemic‐eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…In previous studies, SPA demonstrated a significant change over time and was therefore added to time and intake models ( 15 ). After including SPA, time remained significant in all intake models: total ( β = −51 kcal/year, p < 0.0001), %WMEN ( β = −2%/year, p < 0.0001), protein ( β = −10 kcal/year, p < 0.0001), fat ( β = −23 kcal/year, p < 0.0001), and carbohydrate ( β = −23 kcal/year, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, SPA demonstrated a significant change over time and was therefore added to time and intake models ( 15 ). After including SPA, time remained significant in all intake models: total ( β = −51 kcal/year, p < 0.0001), %WMEN ( β = −2%/year, p < 0.0001), protein ( β = −10 kcal/year, p < 0.0001), fat ( β = −23 kcal/year, p < 0.0001), and carbohydrate ( β = −23 kcal/year, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…In several previously reported studies, as well as our results above, intake was significantly positively associated with SPA that is limited to restless and fidgeting-like behaviors possible in the whole-room calorimeter ( 1 , 5 ). Additionally, Travis et al ( 15 ) demonstrated a secular decline in SPA. If the decline in SPA is representative of an overall decrease in physical activity, this could be reflected in less drive to eat (e.g., reduced activity reducing drive for intake).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations